Digital era generation: Zhai Nan and Zhai Nv blessing or curse - Bano, S. (Institute of Electrical and Electronics Engineers Inc., 2015)
Studies have revealed that technology has become a part of each developmental stage from home to school, school to play time, play time to homework and homework to sleep. The fingerprints of media are presented everywhere as it has become a part of everyone's life. The purpose of this paper is to develop an understanding of a growing subculture of Zhai Nan and Zhai Nv. In particular paper will shed light on the era in which this generation has born and how the things in the environment have transformed because of the advancement of technology and modernization of society. It is very crucial to understand the dynamics of this era before understanding this emerging subculture. The main focus of the study is to comprehend the changing aspects that has played a vital role in the growth of Zhai culture on the basis of literature and how this group lifestyle and values are impacting them at individual and as well as societal level. Â© 2015 IEEE.